PENGARUH KARAKTERISTIK INDIVIDU DAN PENGEMBANGAN KARIR TERHADAP KINERJA PEGAWAI - Hadi Wahyudi; Murdjani Kamaluddin; Sinarwati Sinarwati (Jurnal Manajemen, Bisnis dan Organisasi (JUMBO), 2017)
The purpose of this study were (1) To determine the effect of individual characteristics and career development on the performance of staff  at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi. (2) To determine the effect of individual characteristics on the performance of  staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi. (3) To determine the effect of career development on the performance  of  staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi.Methods of  data analysis  used  were descriptive statistics and multiple linear regression analysis. Samples  used  in the study  were  99 respondents,  which were staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi.The results of  the study showed  that (1) There was a positive, significant effect  of individual characteristics (X1) and career development (X2) on the performance  of  staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi . (2) The individual characteristics (X1) had a positive,  significant effect  on the performance  of  staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi. (3) Career Development (X2)  had a positive,  significant effect  on the performance  of  staff   at the Board  of Social Empowerment and Rural Government of Southeast Sulawesi.Keywords: individual characteristics, career development, staff  performance